Detailed reconstruction for coronary arteries integrating angiographies and IVUS studies - Talou, G. D. Maso; Blanco, P. J.; Larrabide, I.; Bezerra, C. Guedes; Lemos, P. A.; Feijóo, R. A. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2014: Anais do XIV Workshop de Informática Médica, 2014)
The early prediction and/or detection of cardiovascular diseases are of paramount importance worldwide due to the increasing mortality and morbidity rate in the global population. Specifically, key factors for its assessment such as atherosclerotic plaque evolution and vulnerability in coronary arteries are still poorly understood, although in the last decade emerging techniques based on computational models provided a complementary approach towards these problems. To apply these models to patient specific scenarios, a geometric representation of the patient coronary vessels must be accurately constructed in three dimensional space. To achieve this purpose, we present a reconstruction methodology that aims to integrate the high definition provided by intravascular ultrasound about the vessel structure, with the spatial information presented in orthogonal angiographies. As result, the three-dimensional geometric reconstruction of the vessel at different cardiac phases along the cardiac cycle can be obtained, enabling the subsequent development of patient-specific computational models.